Membangun Karakter Siswa Melalui Konseling Pastoral - Sumual, Eunike; Brek, Yohan (PT. Giat Konseling Nusantara, 2024)
This study aims to examine how pastoral counseling can be a solution in building students' character in elementary schools. Through a literature review, this study analyzes various literatures relevant to the topic. The results of the study show that character education currently faces significant challenges, such as the decline of moral values and the negative influence of technology. Pastoral counseling, with its approach to spirituality and religious values, is considered to have great potential in building students' character. This approach can help students develop self-understanding, overcome problems, and find meaning in life. This study concludes that pastoral counseling can be one of the efforts to address the problems of character education in elementary school students